Design of the confined masonry building in Quito, Ecuador - Zhgun, Anna (2018)
This report refers to work completed during my internship with the company IDC Proyectos Integrales that took place in Ecuador, Quito from January, 2018 to July 2018. Ecuador is a country that has a high seismic risk, instability of soils, the great probability of landslides, subsidence, volcanic eruptions, tsunamis and etc. So this is a very challenging place to work for structural engineers. The only way to mitigate the seismic hazard is to design and construct buildings with elements structurally earthquake resistant and also rehabilitation and reconstruction of already existing buildings that were designed before implementing the relevant codes and regulations. During the internship I had an experience with a seismic analysis of different types of structures such as steel frames, arch trusses, concrete frames, masonry buildings. However, for the further development I have chosen the confined masonry building as the most popular type of the construction in Latin America. Due to the recent destructive earthquake that happened in Ecuador on April 16, 2016 with a lot of victims and great number of houses destroyed, buildings in confined masonry could be a good alternative that meets the need for housing construction and reconstruction because of the low cost and low technical complexity of construction. This type of the construction has many advantages, like acoustic, thermal insulation, availability of the material, but at the same way it is very vulnerable to mentioned before nature hazards and it has a height limitation for the construction depending of the seismic risk. This work presents the overview of the masonry and confined masonry structures, its characteristics and behavior during the earthquakes. And as an example of the worldwide experience and the local codes application I present in this report a detailed analysis for the 2-storey confined masonry multifamily building using Ecuadorian, Columbians and American regulations. Moreover the design is performed with a help of the computational program ETABS 2016.